A sea cucumber (Holothuria leucospilota) polysaccharide improves the gut microbiome to alleviate the symptoms of type 2 diabetes mellitus in Goto-Kakizaki rats. (January 2020) - Zhao, Fuqiang; Liu, Qibing; Cao, Jun; Xu, Yunsheng; Pei, Zhisheng; Fan, Haofei; Yuan, Yiqiong; Shen, Xuanri; Li, Chuan
Abstract: Diabetes mellitus has become a worldwide concern in recent years. In this study, the effect of Holothuria leucospilota polysaccharide (HLP) on type 2 diabetes mellitus (T2DM) was investigated in Goto-Kakizaki (GK) rats. The results showed that HLP significantly improved glucose intolerance and regulated blood lipid and hormone levels ( p  < 0.05). Pathological analysis showed that HLP repaired the impairments of the pancreas and colon in diabetic rats. In addition, a high dose of HLP (200 mg/kg) significantly upregulated the gene expression of peroxisome proliferator-activated receptor-α (PPAR-α), peroxisome proliferator-activated receptor-γ (PPAR-γ), phosphoinositide 3-kinase (PI3K), protein kinase B (PKB/AKT), glucose transporter-4 (GLUT4) and anti-apoptotic (Bcl-2), and downregulated the mRNA levels of pro-apoptotic (Bax) and cluster of differentiation 36 (CD36) in diabetic rats ( p  < 0.05). Furthermore, HLP treatment increased the short-chain fatty acid-producing bacteria and decreased the opportunistic bacterial pathogen in the feces of diabetic rats. These results demonstrated that HLP has the potential to ameliorate T2DM in GK rats. Graphical abstract: Image 1 Highlights: HLP decreased the levels of glucose and lipid in diabetic rats. HLP regulated the levels of insulin, adiponectin, leptin and GLP-1. HLP activated the PPARs/PI3K/AKT signaling pathway. HLP regulated the gut microbiota and its metabolites.